2020
DOI: 10.1101/gad.335422.119
|View full text |Cite
|
Sign up to set email alerts
|

Embryo integrity regulates maternal proteostasis and stress resilience

Abstract: The proteostasis network is regulated by transcellular communication to promote health and fitness in metazoans. In Caenorhabditis elegans, signals from the germline initiate the decline of proteostasis and repression of cell stress responses at reproductive maturity, indicating that commitment to reproduction is detrimental to somatic health. Here we show that proteostasis and stress resilience are also regulated by embryo-to-mother communication in reproductive adults. To identify genes that act directly in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 50 publications
8
31
0
Order By: Relevance
“…In addition, DNA damage activates an innate immune response that in turn enhances UPS activity and proteostasis in other tissues ( Ermolaeva et al 2013 ). Finally, a recent study has indicated that developing embryos affect the proteostasis of the hermaphrodite worm carrying them ( Sala et al 2020 ). Together, these surprising observations indicate intertissue communication mechanisms that rewire organismal PNs neuron-independently ( Figure 3 ).…”
Section: Organismal Regulation Of Stress Response and Proteostasismentioning
confidence: 99%
“…In addition, DNA damage activates an innate immune response that in turn enhances UPS activity and proteostasis in other tissues ( Ermolaeva et al 2013 ). Finally, a recent study has indicated that developing embryos affect the proteostasis of the hermaphrodite worm carrying them ( Sala et al 2020 ). Together, these surprising observations indicate intertissue communication mechanisms that rewire organismal PNs neuron-independently ( Figure 3 ).…”
Section: Organismal Regulation Of Stress Response and Proteostasismentioning
confidence: 99%
“…RNA was extracted using TRIzol (Invitrogen) and purified with QIAGEN RNeasy MinElute columns as per manufacturers’ instructions. 44 mRNA was reverse transcribed using the iScript cDNA Synthesis Kit (BioRad) and real-time quantitative PCR was performed using iQ SYBR Green Supermix (BioRad) in a BioRad CFX384 Real-Time PCR system. Relative expression was determined from cycle threshold values using the standard curve method and the expression of genes of interest was normalized to cdc-42 .…”
Section: Methodsmentioning
confidence: 99%
“…The data suggest that there is an embryo-to-mother signaling pathway that regulates the balance between somatic proteostasis and quality of the progeny. 1 The next speaker was Dr. Della David (University of Tübingen, Tübingen, Germany), who presented exciting work detailing for the first time a mechanism by which C. elegans can coordinate extracellular proteostasis through the stress-activated map kinase, KGB1. She showed how the elimination of coelomocytes promotes age-dependent aggregation of lipid-binding protein 2 (LBP-2) in the C. elegans pseudocoelom.…”
Section: Of 6 | Meeting Reportmentioning
confidence: 99%